Prevalence of injuries associated with impacted lower third molars in panoramic radiographs performed in a radiological clinic in the city of Viçosa MG (Research, Society and Development, 2023)
Impaction of permanent teeth occurs when a tooth fails to functionally erupt into the dental arch in the expected time. This is a clinical condition that requires good treatment planning. The etiology of impacted permanent teeth is not fully understood, and may be associated with local and systemic factors. Dental impaction can generate several complications such as disorders in the temporomandibular joints, orofacial pain, neuralgia, resorption or damage to the teeth adjacent to them. This research aimed to study the incidence of these injuries associated with third molars and the indication for their removal in the city of Viçosa (MG) through the study of panoramic radiographs taken in a radiological clinic located in the same. For this, all digital panoramic radiographs taken at the Clinic were used, in the same radiographic device, in the period from 2018 to 2021, with the choice of sampling method being by convenience. Radiographs of both female and male patients aged between 11 years and 6 months to 35 years were selected, at the time of the radiographic examination, who presented one or more lower third molars. A high prevalence of impacted teeth was found. It is important to note among these impacted teeth that there was a large number of associated injuries, indicating the importance of evaluating the indication or not of extractions observing this incidence.